2017
DOI: 10.1158/0008-5472.can-16-1095
|View full text |Cite
|
Sign up to set email alerts
|

MIF-Induced Stromal PKCβ/IL8 Is Essential in Human Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) cells exhibit a high level of spontaneous apoptosis when cultured in vitro but have a prolonged survival time in vivo, indicating that tissue microenvironment plays a critical role in promoting AML cell survival. In vitro studies have shown that bone marrow mesenchymal stromal cells (BM-MSC) protect AML blasts from spontaneous and chemotherapy-induced apoptosis. Here, we report a novel interaction between AML blasts and BM-MSCs, which benefits AML proliferation and survival. We ini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 43 publications
1
49
0
Order By: Relevance
“…Preclinical studies of milatuzumab have shown potent efficacy in hematopoietic neoplasms primarily occupying the BM niche, such as CLL/SLL, PCM, and AML . All CLL/SLL in the current study expressed CD74.…”
Section: Discussionmentioning
confidence: 64%
“…Preclinical studies of milatuzumab have shown potent efficacy in hematopoietic neoplasms primarily occupying the BM niche, such as CLL/SLL, PCM, and AML . All CLL/SLL in the current study expressed CD74.…”
Section: Discussionmentioning
confidence: 64%
“…1). In recent years, several studies have shown a paracrine effect of MSC‐secreted CXCL8 on tumors (3032). Therefore, we also analyzed the CXCL8 expression levels in the MSCs obtained from the ex vivo expansion of BM cells from the patients and control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown increased synthesis of proinflammatory cytokines and chemokines, including that of CXCL8, in BM‐MSCs stimulated with cancer cells in vitro (32, 41, 42). Consistent with this, we found increased mRNA levels of CXCL8 in MSCs and AML cell cocultures compared with that of either monoculture.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high invasive potency of synovial sarcoma cells towards the surrounding tissue, it is possible that IL-8 contributes to the invasive activity of the tumor cells by interacting with the tumor microenvironment. Indeed, increased secretion of IL-8 secretions has been reported in various human malignancies, and IL-8 is involved in more aggressive phenotypes [38][39][40][41]. Functional modulation of tumor-associated neutrophils by IL-8 has also been described as a poor prognostic factor for malignancies [39,42].…”
Section: Discussionmentioning
confidence: 99%